2007
DOI: 10.2478/s11658-006-0068-5
|View full text |Cite
|
Sign up to set email alerts
|

Tetraploid somatic hybrids of potato (Solanum tuberosum L.) obtained from diploid breeding lines

Abstract: Intraspecific somatic hybrids between 16 different diploid breeding lines of Solanum tuberosum L. were produced by PEG-induced fusion. Manually selected heterokaryons were cultured in a Millicells-CM using a postfusion protoplast mixture. Plants were regenerated from calli derived from heterokaryons obtained from 10 out of 38 combinations of diploid lines. Of the tested putative somatic hybrids, 14.2% were diploid, 72.8% were tetraploid and 13% pentaploid. The DNA amplification pattern obtained with RAPD or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Electrofusion and PEG induced fusion are equally effective methods (Orczyk et al 2003) and the result of protoplast fusion mainly depends on efficient fusion protocol. Przetakiewicz et al (2007) produced somatic hybrids between diploid interspecific hybrids using PEG method. Szczerbakowa et al (2010) applied this approach to obtain the first set of 13 somatic hybrids between clone mch /8 and clone DG 81-68.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrofusion and PEG induced fusion are equally effective methods (Orczyk et al 2003) and the result of protoplast fusion mainly depends on efficient fusion protocol. Przetakiewicz et al (2007) produced somatic hybrids between diploid interspecific hybrids using PEG method. Szczerbakowa et al (2010) applied this approach to obtain the first set of 13 somatic hybrids between clone mch /8 and clone DG 81-68.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DG 88-89 had S. gourlayi in origin. They were male fertile, producing functional 2 n male gametes, and useful for protoplast fusion with other diploids (Przetakiewicz et al 2007). Dihaploid dH Bard derived from cv.…”
Section: Methodsmentioning
confidence: 99%
“…No cpDNA alterations were noticed (Pehu et al 1989; Xu and Pehu 1993; Cardi et al 1999) in contrast to mtDNA, where recombination is often observed (Lössl et al 1994). In some cases, no recombination of mtDNA was detected (Przetakiewicz et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The insect's salivary gland epithelial cells migrate to their location only after myoblasts, longitudinal muscle founder cells and other mesenchymal cells fused and provided the proper integrins (258,259). Interspecies hybridization by cell fusion in fishes (carp) resulted in allo-tetraplod hybrid cells of great significance in genetic research for fish breeding (260), Plant (Solanum) mesophyll cell protoplasts can be fused in vitro with PEG (polyethylene glycol), remain stable as tetra-to decaploid cells, grow in soil, set flowers and bear parthenocarpic (virgin fruit) berries (261)(262)(263). This technology is applicable to many fruit-bearing plants.…”
Section: Discussion: Physiology Pathophysiology Therapeuticsmentioning
confidence: 99%